SimGest: A simulation experimentation environment and a program generator for interactive simulation. - Jin, Qiang. (University of Ottawa (Canada), 1994)
A good methodology for simulation experimentation can result in high efficiency in carrying out simulation experiments. To fully support a user to carry out a simulation experiment, a supportive and user friendly simulation experimentation environment is desirable. The program generator which generates the executable programs from a model expressed in a high-level simulation programming language is another important issue in simulation experimentation. This thesis presents a new methodology for simulation experimentation based on the model specification language Gest. A simulation experimentation environment which supports a user to carry out the simulation experiment based on the model written in Gest is implemented. A program generator which analyzes the model and generates an executable simulation program with simulation tables for the simulation experimentation environment is also discussed.
Keywords: Computer Science.